2023
DOI: 10.1038/s41522-023-00464-7
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic stress stimulates eDNA release via explosive cell lysis and thereby promotes streamer formation of Burkholderia cenocepacia H111 cultured in a microfluidic device

Zaira Heredia-Ponce,
Eleonora Secchi,
Masanori Toyofuku
et al.

Abstract: DNA is a component of biofilms, but the triggers of DNA release during biofilm formation and how DNA contributes to biofilm development are poorly investigated. One key mechanism involved in DNA release is explosive cell lysis, which is a consequence of prophage induction. In this article, the role of explosive cell lysis in biofilm formation was investigated in the opportunistic human pathogen Burkholderia cenocepacia H111 (H111). Biofilm streamers, flow-suspended biofilm filaments, were used as a biofilm mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Prophage endolysin–triggered explosive cell lysis has been proposed as a new mechanism for membrane vesicle production [ 74 ]. Stresses, including ciprofloxacin and MMC, can induce and promote explosive cell lysis events [ 75 ]. In this study, we found that the release of Phm3 was accompanied by OMV production, which was not observed during Phm1 or Phm2 phage release.…”
Section: Discussionmentioning
confidence: 99%
“…Prophage endolysin–triggered explosive cell lysis has been proposed as a new mechanism for membrane vesicle production [ 74 ]. Stresses, including ciprofloxacin and MMC, can induce and promote explosive cell lysis events [ 75 ]. In this study, we found that the release of Phm3 was accompanied by OMV production, which was not observed during Phm1 or Phm2 phage release.…”
Section: Discussionmentioning
confidence: 99%